(untitled) - Campbell, A. Malcolm; A. Malcolm Campbell; Laurie J. Heyer (San Francisco)
Discovering Genomics, Proteomics, and Bioinformatics combines integrated Web exercises with a problem-solving approach to train readers in basic hands-on genomic analysis. The authors present global problems, then provide the tools of genomic analysis to help readers dissect the answer, thus encouraging critical thinking skills. Short boxed readings called "Math Minutes" explain the math behind the biology. KEY TOPICS: GENOMIC SEQUENCES, GENOMIC EXPRESSION, WHOLE GENOME PERSPECTIVE, TRANSITION FROM GENETICS TO GENOMICS: MEDICAL CASE STUDIES. For anyone interested in genomics, proteomics, or bioinformatics
Includes bibliographical references and index
Keywords: Genomics; Proteomics; Bioinformatics